Atomic Force Microscopy Investigation of the In Situ‐Formed Oxide Layer at the Interface of Al2O3−C/Steel Melt in Terms of Adhesion Force and Roughness in a Model System. Issue 2 (20th November 2021) - Ditscherlein, Lisa; Zienert, Tilo; Dudczig, Steffen; Aneziris, Christos; Peuker, Urs Alexander
Abstract : Herein, the in situ‐formed layers on carbon‐bonded alumina refractories immersed in liquid 42CrMo4 steel at 1650 °C are investigated with regard to their macro‐ and microroughness, wetting properties, as well as adhesive interactions. Colloidal probe (CP) atomic force microscopy (AFM) are used to describe the adhesion in a water‐based model system. To take the interaction between melt and the in situ layer into account, the adhesive force is measured via drop probe AFM using a model system with mercury droplets. For poorly wetted in situ layer samples, adhesion forces increase with smaller hold times in the melt due to a less homogeneous layer and vice versa if only van der Waals forces act. In contrast, the influence of the immersion time in the melt and the lattice parameter of the crystals on the layer is of minor importance for melt droplet−layer adhesion. Abstract : This publication deals with the investigation of the in situ‐formed alumina/spinel layer on Al2 O3 −C samples. Roughnesses and contact angle measurements show no significant dependence on hold time in the melt or lattice parameter. These factors influence van der Waals and capillary forces measured by AFM in the model system. The modeling results agree well with the experiment.